Health-related quality of life of alcohol use disorder with co-occurring conditions in the US population. (1st April 2021) - Wittenberg, Eve; Barbosa, Carolina; Hein, Riley; Hudson, Emma; Thornburg, Benjamin; Bray, Jeremy W.
Highlights: AUD commonly occurs in tandem with other conditions. Co-occurring conditions show lower health related quality of life (HRQoL) than AUD. HRQoL of AUD with other conditions can be used in cost-effectiveness analysis (CEA). Patient-centered care for AUD considers the whole person, with other conditions. Abstract: Background: Alcohol use disorder (AUD) commonly co-occurs with other health conditions or other substance use, complicating our understanding of the health-related quality of life (HRQoL) of AUD. We described the HRQoL of alcohol use disorder in the presence of co-occurring conditions and identified the contribution of each. Methods: Secondary analysis of National Epidemiologic Survey on Alcohol and Related Conditions III data, consisting of 36, 309 non-institutionalized US adults; descriptive and regression analysis. HRQoL measured via the SF-6D; AUD via the Alcohol Use Disorder and Associated Disabilities Interview Schedule (AUDADIS-5); physical, mental health, and substance use disorders/conditions as reported or assessed via AUDADIS-5. Results: AUD was independently associated with lower HRQoL for individuals experiencing co-occurring conditions. Compared to no AUD, past year AUD reduced SF-6D score by 0.0304 (SE = 0.0027) and prior-to-past-year AUD reduced SF-6D by 0.0163 (SE = 0.0023). AUD's co-occurring conditions were independently associated with lower HRQoL, beyond the reduction from AUD: any co-occurring physical health condition was associated with a 0.062 point reduction in SF-6D score (SE = 0.0023), any mental health condition with a 0.084 point reduction (SE = 0.0025), and any substance use disorder with a 0.038 point reduction (SE = 0.0023). Conclusions: AUD's association with diminished HRQoL may be explained in large part by the presence of co-occurring conditions among individuals reporting AUD, as these co-occurring conditions are associated with substantial decrements in HRQoL—often eclipsing the magnitude of the decrements associated with AUD alone. Alcohol use interventions endeavoring to improve HRQoL should consider the entirety of an individual to design patient-centered care.